Uma abordagem dialógica para a utilização de atividades experimentais em sala de aula - Silva Junior, José Ferreira da (2010)
The belief of using experimental activities in the teaching of Physics as a strategy to produce a more efficient teaching-learning process is great among teachers and the school community. However, there are many difficulties for their implementation and when it happens they do not contribute for an improvement in class efficiency due to the method used. In this work, we developed a proposal for using these activities in Physics classes in high school, from a critical-reflexive approach in which the constant dialogue between the participants in the teaching-learning process is fundamental. The work was developed in two ways. The first, where the author/writer created an educational material and applied it in classroom and a second one, where he presented the idea to other teachers and undergraduate students from the Physics course at UFRN and IFRN (former CEFET-RN) through an extended workshop entitled "The role of experimental activities in the Physics teaching". This workshop had the duration of 60 hours and was implemented in 4 steps: i) sensitization and formation, ii) material development, iii) material implementation and iv) evaluation by teachers and students from the classes where the material was applied. The goal of this workshop was to present the approach, evaluate how the participants received the idea and how they would apply it in real situations. The results of the application in classroom allowed us to reach some conclusions. This approach was well received by the students as well as by the workshop participants. Despite some difficulties in relation to the handling of the implementation results by the workshop participants, they indicated changes in these professionals teaching practice and the introduction of experimental activities has been an important subsidy to assist them in Physics class in high school